Innovative UI/UX Analysis of Cooperative Apps through Design Thinking - Fanani, Rizki Dwi; Wiguna, I Komang Arya Ganda; Iskandar, Adi Panca Saputra; Parwita, Wayan Gede Suka (Yayasan Sraddha Panca Widya Nusantara, 2024)
Radha Krisna Savings and Loan Cooperative operates as an entity affiliated with Krisna Holding Company, more commonly referred to as Krisna Oleh-oleh. Although Radha Krisna Savings and Loan Cooperative has been in operation since 2010, it did not begin utilising a desktop application as its information system until 2014. This application has since been employed to facilitate a variety of transaction processes. The issue at the Radha Krisna Savings and Loan Cooperative is that the utilised application has begun to fail to support user requirements for transactions, as certain menus, features, user interface, and user experience continue to fall short of user expectations. In light of this issue, it is imperative to conduct an analysis of the collaborative application and construct a prototype that satisfies the diverse requirements of users, serving as a benchmark for the improvement of forthcoming applications. Utilising the Design Thinking method, prototype development consists of the following phases: Emphasise, Define, Ideate, Prototype, and Test. Figma is the instrument utilised for prototyping. A User Experience Questionnaire (UEQ) is administered to a sample of eight managers from the Radha Krisna Savings and Loan Cooperative as part of the testing phase. Based on the Benchmark Data, the average value for the attractiveness scale is 2.01 (Excellent), the average value for clarity is 2.31 (Excellent), the average value for efficiency is 1.91 (Excellent), the average value for accuracy is 1.81 (Excellent), the average value for stimulation is 2.06 (Excellent), and the average value for novelty is 1.94 (Excellent).